Antibacterial and anti-inflammatory potential of three sea cucumber species from Tukuran, Zamboanga del Sur, Mindanao, Philippines (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ereguero MG, Gelani C, Dalayap R, Cordero MA, Tabugo SR. 2023. Antibacterial and anti-inflammatory potential of three sea cucumber species from Tukuran, Zamboanga del Sur, Mindanao, Philippines. Biodiversitas 24: 2527-2535. The marine environment is a rich source of potential antibacterial and anti-inflammatory agents. This study investigated three sea cucumber species' antibacterial and anti-inflammatory activity from Tukuran, Zamboanga del Sur, Philippines. The methanol: ethyl acetate crude extracts of Holothuria scabra, Stichopus sp., and Holothuria atra were tested for their antibacterial activity against gram-negative (Pseudomonas aeruginosa, Escherichia coli) and gram-positive (Staphylococcus aureus, Bacillus subtilis) bacteria using modified microtiter plate method. Results revealed that sea cucumber extracts have MIC values of 0.0008-0.0944 mg/mL. One-way ANOVA results revealed a p value
Keywords: Albumin denaturation, MIC, microtiter resazurin, sea cucumber